The traditional uses, pharmacology, and phytochemistry of Peucedanum praeruptorum Dunn - Wang, Qiongxiao; Sun, Qingmei; Huang, Qinger; Qin, Luping; Zhu, Bo (Frontiers in Pharmacology, 2024)
Bai Hua Qian Hu (Qianhu; Peucedanum praeruptorum Dunn) is a classical medicinal plant traditionally prescribed for respiratory ailments, including cough, pulmonary hypertension, and asthma. In this review, we summarize the research progress of the toxicology, pharmacokinetics, pharmacology, phytochemistry, botany, quality control, and traditional uses of P. praeruptorum in order to support future investigations into the scientific and therapeutic promise of this important medicinal plant. Information pertaining to P. praeruptorum was collected from scientific databases (ScienceDirect, Springer, SciFinder, PubMed, Baidu Scholar, Google Scholar, Web of Science), as well as toxicology papers from local conferences, M.Sc. and Ph.D. theses and dissertations, local magazines, classic texts on Chinese botanical drugs, and peer-reviewed journals. The Plant List (www.theplantlist.org) was utilized to verify the taxonomy of P. praeruptorum. P. praeruptorum was found to contain more than 119 distinct phytochemicals, including simple coumarins, pyranocoumarins, furanocoumarins, flavonoids, ketones, organic acids, and sterols, among others (e.g. praeruptorins A and B). Both crude plant extracts and purified metabolites of P. praeruptorum have been reported as treatments for hypertension, osteoporosis, Huntington's disease, and cancer.In addition, extracts of P. praeruptorum are reported to exhibit diverse pharmacological activities, including osteogenic, anti-osteoclastogenic, antidepressant, neuroprotective, antitumor, and antiinflammatory effects. Research into the pharmacology and phytochemistry of P. praeruptorum partially support both traditional uses and extraction methods. However, further research is required to elucidate the relationships between these metabolites, their molecular mechanisms, their structure-function roles, and their antagonistic and synergistic effects.